Elder Mistreatment: Implications for Public Health Dentistry - Howard J. Cowen, DDS, MS; Perle Slavik Cowen, RN, PhD (Blackwell Synergy, 2001)
Elder mistreatment has increasingly been recognized as a serious and complex health issue affecting large numbers of elders each year. Health professionals have been found to lack knowledge regarding assessment, diagnosis, intetvention, and reporting criteria of this problem. In dentistry, there have been recent calls formore research and publications as wellas requests forprofessional policy statements and guidelines. Public health dentistry, with its emphasis on prevention, can lend guidance and leadership at the primary, secondary, and tertiary levels. This article reviews the types and prevalence of elder mistreatment, discusses predisposing variables, and offers an ecological model that serves as a guide to interventions directed at all levels of elder mistreatment prevention.